Fases de erupción y posición más frecuentes de terceros molares incluidos. Riobamba 2018 - Castillo Alcoser, Carla Margarita (2019)
The prevalence of third molars worldwide stands for more than 30%. The objective of this research project was to analyze the most frequent eruption and position phases of the third molars by including some patients’ panoramic radiographs who have attended private dental clinics in Riobamba city, from 2015 to 2018. The study was observational, descriptive, retrospective and cross-sectional type. The data were processed by SPSS v.25 program. Its purpose was to identify the prevalence of bad position of this kind of tooth. The Moyers eruption phases and the Pell & Gregory and Winter classification were taken as a reference. They allowed conducting an observation, analysis and data collation of 172 panoramic radiographs in total. Those panoramic radiographs were selected by inclusion and exclusion criteria. As a result, maxillary third molars prevail class I, level C and in a vertical position; meanwhile mesioangular position is more frequent in the jaw. It means class II and level B. Regarding the eruption phases, it was observed that in both genres, Functional eruptive phase is developed between 18 and 35 years. There are some atypical cases on which some patients still kept the third molars even after 40 years. It was also observed third molars agenesis, especially of the maxilla. It was also shown that there were no statistically significant differences between the eruption phase groups in relation to age (p = 0.00, CI = 0,95).